Burdening or boosting thematic subjects: students’ team-assisted individualization learning model - Rodhiyah, Syifa Robby; Sumekto, Didik Rinan; Setyawati, Heny; Setiawan, Ari (Intelektual Pustaka Media Utama, 2024)
Team-assisted individualization (TAI) learning accommodates the primary school students’ learning activities through the cooperative and individual learning models. The study aims at investigating students’ TAI cooperative and conventional learning models among third-graders’ thematic subjects two public primary schools in Klaten district, Indonesia. A quasi-experimental research design was applied by involving 20 experiment and 18 control groups respectively. Data collection used the multiple-choice tests of thematics subjects to measure the third-graders’ TAI cooperative and conventional learning in arts, culture, and life skills and Indonesian subjects. Data analysis used a non-parametric statistic to prove the mean difference test in two or more groups, descriptive test, T-tests, Mann Whitney-U test, and N-gain test. The results showed an increase in the experiment group higher than in the control group. However, there was no significant difference between the experiment and control groups after examining the multiple-choice tests. The results supported the thematic subjects of the characteristics of living things in arts, culture, and life skills, and Indonesian teaching since proving the third-graders’ learning improvement naturally and objectively. This study concludes that TAI’s cooperative and conventional learning models accommodate the learning activities although its implication does not contribute significantly.